PREDIKSI CURAH HUJAN PELABUHAN TANJUNG MAS SEMARANG DENGAN METODE SINGLE EXPONENTIAL SMOOTHING - Dedi, Widiarto; Widiyanto Tri, Handoko (Information Technology and Telematics, 2018)
Abstract- Weather and climate are a process of phenomena in the atmosphere whose existence is very important in various life activities. Attention about weather and climate information is increasing along with the increase of natural phenomena that are not commonly occurring or commonly referred to as extreme weather which is difficult to control and modify. Rainfall data is very interesting to study because rainfall is one of the biggest factors that affect the climate of a region and affect various sectors of human life. Rainfall prediction can be done using data mining System development method used in this research is Waterfall which consists of the beginning of the system, system analysis, system design using UML and implementation using PHP and MySQL.The final result of this research is the result of Tanjung Mas Port rainfall prediction Semarang using exponential smoothing method with a value of α = 0.5 obtained MSE value of 3.490, value α = 0,7 obtained MSE value of 3.964 and α value = 0.9 obtained MSE value of 4.497. Of the three values ​​α = 0.5, α = 0.7 and α = 0.9, the smallest MSE value is α = 0.5 so that the rainfall prediction at Tanjung Mas Semarang uses a value of α = 0.5.